Comprehensive Fragment Screening of the SARS‐CoV‐2 Proteome Explores Novel Chemical Space for Drug Development. Issue 46 (13th October 2022) - Berg, Hannes; Wirtz Martin, Maria A.; Altincekic, Nadide; Alshamleh, Islam; Kaur Bains, Jasleen; Blechar, Julius; Ceylan, Betül; de Jesus, Vanessa; Dhamotharan, Karthikeyan; Fuks, Christin; Gande, Santosh L.; Hargittay, Bruno; et al.
Abstract: SARS‐CoV‐2 (SCoV2) and its variants of concern pose serious challenges to the public health. The variants increased challenges to vaccines, thus necessitating for development of new intervention strategies including anti‐virals. Within the international Covid19‐NMR consortium, we have identified binders targeting the RNA genome of SCoV2. We established protocols for the production and NMR characterization of more than 80 % of all SCoV2 proteins. Here, we performed an NMR screening using a fragment library for binding to 25 SCoV2 proteins and identified hits also against previously unexplored SCoV2 proteins. Computational mapping was used to predict binding sites and identify functional moieties (chemotypes) of the ligands occupying these pockets. Striking consensus was observed between NMR‐detected binding sites of the main protease and the computational procedure. Our investigation provides novel structural and chemical space for structure‐based drug design against the SCoV2 proteome. Abstract : Using a fragment‐based screening strategy by NMR, we identified 311 small molecule binders of 25 SARS‐CoV‐2 proteins, thus expanding the previously unexplored chemical and target space. Further, using experimental and bioinformatic analysis we identify potential binding sites. This comprehensive data would greatly assist medicinal chemistry efforts even beyond COVID‐19.